Larvicidal Efficacy of Citrus Sinensis Extracts on Laboratory Strains of Aedes aegypti and Culex quinquefasciatus - Muthuraman, A.; Shajahan, A.; Hussain, M.I. Zahir; Venkatesh, B. Pon (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Mosquito-borne diseases pose significant global health risks, particularly in tropical regions. Aedes and Culex mosquitoes are key vectors for diseases like dengue, Zika, and West Nile virus. This study explores the larvicidal potential of orange peel (Citrus sinensis) extracts against Ae. aegypti and Cx. quinquefasciatus mosquitoes. Extracts were prepared using acetone, methanol, hexane, and petroleum ether and their respective efficacy was tested on Ae. aegypti and Cx. quinquefasciatus larvae. Larvicidal assays revealed that the hexane extract exhibited the highest efficacy, with LC50 values of 13.24 ppm for Ae. aegypti and 38.82 ppm for Cx. quinquefasciatus, achieving up to 98% and 95% mortality rates at 100 ppm, respectively. The petroleum ether extract was notably effective against Cx. quinquefasciatus, while acetone and methanol extracts showed moderate efficacy. Statistical analysis, including Probit analysis, confirmed the significance of these findings. These findings suggest that orange peel extracts, particularly hexane, could serve as effective, eco-friendly larvicides, offering a sustainable alternative to traditional mosquito control methods.